2012
DOI: 10.2134/agronj2011.0327
|View full text |Cite
|
Sign up to set email alerts
|

Biosolids from Treated Swine Manure and Papermill Residues Affect Corn Fertilizer Value

Abstract: Biosolids derived from treatment of animal manure or industrial effl uents can be used on farms, but their fertilizer value must be assessed. A 3-yr fi eld study was conducted on a clay soil in Quebec, Canada, to evaluate the eff ect of several biosolids on silage corn dry matter (DM) yield; N-use effi ciency; and soil N, P, Cu, and Zn availability. Raw liquid swine (Sus scrofa) manure (LSM), biosolids from four swine manure treatments (aerobic digestion [AER], anaerobic digestion [DIG], fi ltration [FIL], ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 36 publications
(46 reference statements)
2
25
0
Order By: Relevance
“…The three pellet types showed significant differences (p < 0.05) between 10, 20, and 40 Mg ha -1 , especially Pellet 1, which contained a higher proportion of fly ash. The highest pH values occurred at the highest dose of 40 Mg ha -1 in amended soil (Gagnon et al, 2012;Brannvall et al, 2015). This indicated that pellets containing fly ash can correct the acidity of degraded soil; on average, 0.1 pH unit per 5.5 Mg pellets was the result in the studied Alfisol that showed low buffer capacity.…”
Section: Nutrient Input From Three Pellet Types Incubated In a Degradmentioning
confidence: 87%
“…The three pellet types showed significant differences (p < 0.05) between 10, 20, and 40 Mg ha -1 , especially Pellet 1, which contained a higher proportion of fly ash. The highest pH values occurred at the highest dose of 40 Mg ha -1 in amended soil (Gagnon et al, 2012;Brannvall et al, 2015). This indicated that pellets containing fly ash can correct the acidity of degraded soil; on average, 0.1 pH unit per 5.5 Mg pellets was the result in the studied Alfisol that showed low buffer capacity.…”
Section: Nutrient Input From Three Pellet Types Incubated In a Degradmentioning
confidence: 87%
“…Similar corn silage yields were observed with either digested manure or undigested manure. However, crop nitrogen utilization from the organic fertilizers was only 70% as efficient as crops using mineral nitrate fertilizers (Gagnon et al, 2012). Loria et al (2007) showed that digested and raw swine manure were not significantly different as a source of nitrogen for growing corn.…”
Section: Land Application For Crop Productionmentioning
confidence: 99%
“…As shown in Table 2, several crops including maize, silage (Gagnon et al, 2012), ryegrass (Fouda et al, 2013), legumes (Bougnom et al, 2012), and fruits (Yu et al, 2010) have been successfully grown using AD effluent as an organic fertilizer. The local climate, physical and biological soil properties, AD effluent composition, nitrogen application rates, plant-available nitrogen, crop types, and crop rotations substantially affected plant yield and nitrogen uptake.…”
Section: Land Application For Crop Productionmentioning
confidence: 99%
See 2 more Smart Citations